The Risk Factors-Based Nursing Case Management Could Ef-fectively Reduce the Incidence of Pressure Sores in Hospitalized Patients - Hong JIANG; Yanwen LIANG; Xinmei LIU; Donghong YE; Mengmiao PENG; Yun CHEN; Shuang CHEN; Wanying CHEN; Haiyan LI; Shuyao ZHANG (Tehran University of Medical Sciences, 2021)
Background: To explore the effects of risk factors-based nursing management on the occurrence of pressure sores in hospitalized patients. Methods: From Jan 2018 to Jun 2018, 289 hospitalized patients were divided into pressure sores group [100] and control group [189] for retrospective analysis. Overall, 260 hospitalized patients from Jun 2018 to Dec 2018 were followed up for nursing intervention. Overall 130 patients received risk factors-based nursing case management were in the intervention group, whereas 130 patients who received routine nursing care were in the control group. The chi-square test and t-test were used to compare the count data and the measurement data between groups, respectively. Results: Age, body weight and proportions of patients with impaired nutritional intake, diabetes or stroke in pressure sores group were higher than those in normal group (P<0.05). Hospital stay and operative time in pressure sores group was longer than those in normal group (P<0.05). The frequency of assistant activity in pressure sores group was significantly lower than that in control group (P<0.05).In addition, the score of uroclepsia in pressure sores group was lower than that in normal group (P<0.05). Patients in the intervention group showed lower risk for pressure sores and more satisfied than patients in control group (P<0.001). Conclusion: Advanced age, high body weight, diabetes and stroke, long hospital stay, long operative time, poor nutritional status and severe uroclepsia were independent risk factors of pressure sores. Risk factors-based nursing case management can effectively reduce the occurrence and risk of pressure sores for hospitalized patients.